(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This report presents the results of a study of the development of the marine litter monitoring system in Bulgaria in the period 2016-2022. The system has been structured and operates as part of the implementation of the requirements of the Marine Strategy Framework Directive 2008/56/EC and in particular Descriptor 10 “Marine litter”. Until 2022, the monitoring surveys of the distribution, abundance and accumulation of marine litter were carried out in accordance with specific criteria for macro- and micro-litter. In parallel, the potential sources of marine litter and the pressure of its introduction into the marine environment, beaches, water column and seabed have been analyzed. A comprehensive comparative analysis has been conducted in regards to the applied monitoring procedures, as well as the results of numerous monitoring surveys conducted in the frames of Bulgarian national marine litter monitoring system, during the studied period. As a result the main challenges for the development and the upcoming increase in the scope of the system were identified end presented in this paper. Opportunities to improve the functioning of the system, directed to eliminating weaknesses in relation to used observation protocols, monitoring sites, frequency of monitoring, ensuring representativeness and comparability of monitoring data and information are listed.